Situação do estágio supervisionado em IES privadas da grande São Paulo Supervised period of training on the private universities of São Paulo and cities of the region - Sheila Aparecida Pereira dos Santos Silva; César Augusto Fernandes de Souza; Felipe Marques Checa (Universidade Estadual Paulista (UNESP), 2010)
Com o objetivo de diagnosticar a dinâmica da supervisão dos estágios em cursos de Graduação e Licenciatura em Educação Física após a publicação das Resoluções CNE/CP nº 01 e 02/2002, nº 07/2004 e nº 02/2007 e verificar sua aplicação, foram entrevistados sete docentes universitários, que orientam estágios curriculares em seis Instituições de Ensino Superior (IES) privadas da Grande São Paulo. A entrevista, semi-estruturada, contou com sete questões abertas abrangendo a dinâmica dos estágios, carga horária, número de orientadores por aluno orientado, entre outros aspectos. Para o tratamento dos dados, foi utilizada a técnica de análise de conteúdo. Em todas as instituições pesquisadas o estágio é exigido a partir da metade do curso; existiam projetos de pesquisa e extensão que eram validados como horas/estágio e contemplavam uma disciplina destinada aos estágios, à exceção de uma delas. As horas de estágio a cumprir variaram entre 324 a 540 horas. Existiam diferenças significativas em relação ao número de orientandos por orientador, variando de 5 a 200 alunos por orientador. Em apenas uma IES ocorriam discussões sobre os relatórios apresentados. Percebeu-se a inexistência de uniformidade entre as instituições pesquisadas e, em algumas, a ausência de discussões a respeito dos estágios evidencia que as IES pouco se comprometem com a qualidade dessa experiência no processo de formação profissional e que, talvez, normas legais mais específicas sobre número máximo de alunos orientados por orientador pudessem colaborar para que esse problema fosse minimizado With the objective to make a diagnosis the dynamics of the supervision of the periods of training in courses of Graduation in Physical Education after the publication of Resolutions CNE/CP nº 01 and 02/2002, nº 07/2004 and nº 02/2007 and to verify its application, had been interviewed seven university professors, who guide curricular periods of training in six Institutions of Universities privates of the Great São Paulo. The interview, half-structuralized, counted on seven open questions enclosing the dynamics of the periods of training, hours of duration, number of pupils guided for each teacher, among others aspects. For the treatment of the data, the technique of content analysis was used. In all the searched institutions the period of training is demanded from the half of the course; projects of research and extension that were validated as hours/period of training and contemplated one discipline destined to the periods of training, to the exception of one of them. The hours of period of training to fulfill had varied between 324 and 540 hours. Significant differences in relation to the number of guided persons varying between 5 to 200 students for teacher who orientates. In only one University quarrels occurred on the presented reports. It was perceived inexistence of uniformity between searched institutions and, in some, the absence of quarrels regarding the periods of training evidences that the Universities have a little committed with the quality of this experience in the process of professional formation and that, perhaps, more specific rules of law on maximum number of pupils guided for person who orientates could collaborate so that this problem was minimized.